Impact on refractive surgery due to increasing use of personal protection equipment: Insights from EUROCOVCAT group. Issue 6 (November 2021) - Cummings, Arthur B; Gildea, Cian; Brézin, Antoine P; Malyugin, Boris E; Evren Kemer, Ozlem; Kermani, Omid; Prieto, Isabel; Rejdak, Robert; Teus, Miguel A; Tognetto, Daniele; Zweifel, Sandrine; Toro, Mario D
Since the World Health Organization declared COVID-19 to be a pandemic on 11th March 2020, changes to social and sanitary practices have included significant issues in access and management of eye care during the COVID-19 pandemic. Additionally, the fear of loss, coupled with social distancing, lockdown, economic instability, and uncertainty, have led to a significant psychosocial impact that will have to be addressed. In the current COVID-19 pandemic, personal protective equipment such as face masks or face coverings have become a daily necessity. While "mass masking" along with hand hygiene and social distancing became more widespread, new issues began to emerge – particularly in those who wore spectacles as a means of vision correction. As we began to see routine patients again after the first lockdown had been lifted, many patients visited our clinics for refractive surgery consultations with a primary motivating factor of wanting spectacle independence due to the fogging of their spectacles as a result of wearing a mask. In this article, we report on new emerging issues in eye care due to the widespread use of masks and on the new unmet need in the corneal and cataract refractive surgery fields.